Knowledge About HIV And AIDS Among Medical Entrants - A Questionnaire Study - Chatterjee Gobinda; Chakraborthy Indranil; Mitra (Ghosh) (Wolters Kluwer Medknow Publications, 2001)
A close ended questionnaire study on knowledge attitude and practice (KAP) about HIV/AIDS was conducted amongst first year MBBS students immediately on joining the course. One hundred and fourteen students participated in the study. Overall level of knowledge about AIDS was found to be 72%. Boys were better informed about possible methods of prevention of AIDS than girls. Misconceptions regarding mode of transmission, clinical presentation and prevention existed amongst large number of them. Seventeen percent of boys and 5% of girls approved of pre-marital sex for boys while 14.8% of boys approved the same for girls. Thirteen and half percent of boys admitted sexual experience. Awareness programme should be intensified amongst students to improve the overall knowledge of AIDS.